Association between neuromuscular tests and kumite performance on the Brazilian karate national team - Roschel, H.; Batista, M.; Monteiro, R.; Bertuzzi, R. C.; Barroso, R.; Loturco, I.; Ugrinowitsch, C.; Tricoli, V.; Franchini, E. (Journal of Sports Science & Medicine, 2009)
The aim of this study was to verify the relationship of strength and power with performance on an international level karate team during official kumite simulations. Fourteen male black belt karate athletes were submitted to anthropometric data collection and then performed the following tests on two different days: vertical jump test, bench press and squat maximum dynamic strength (1RM) tests. We also tested power production for both exercises at 30 and 60%1RM and performed a kumite match simulation. Blood samples were obtained at rest and immediately after the kumite matches to measure blood lactate concentration. Karate players were separated by performance (winners vs. defeated) on the kumite matches. We found no significant differences between winners and defeated for strength, vertical jump height, anthropometric data and blood lactate concentration. Interestingly, winners were more powerful in the bench press and squat exercises at 30% 1RM. Maximum strength was correlated with absolute (30% 1RM r = 0.92; 60% 1RM r = 0.63) and relative power (30% 1RM r = 0.74; 60% 1RM r = 0.11, p > 0.05) for the bench press exercise. We concluded that international level karate players' kumite match performance are influenced by higher levels of upper and lower limbs power production.